Origins, pathophysiology, diagnosis, vaccination and prevention of Chikungunya virus - Rafe, Md. Rajdoula; Ahmed, Syeda Naureen; Ahmed, Zebunnesa (Current Issues in Pharmacy and Medical Sciences, 2019)
Chikungunya virus is an Alphavirusthat possesses characteristics similar to that of an arthropod-borne virus. Chikungunya virus has been one of the major concerns for the last few decades due to its nature of explosive spreading throughout the world. This article is intended to give detailed information about Chikungunya virus, and includes its pathogenesis, origins, diagnosis, treatment and prevention. Although, recent researches suggests various approaches to treating Chikungunya virus, extensive literature search on Chikungunya virus has revealed that, currently, there is no effective treatment available and the virus is greatly dependent on its vectors. Patients affected by Chikungunya virus mainly show symptoms of fever, arthralgia, joint pain and skin rash. Since there is no effective treatment available, public awareness is the most significant factor for potential prevention against Chikungunya virus.